First record of order Embioptera (Insecta) for the State of Tocantins, Brazil, with description of a new species of Clothoda Enderlein - Krolow, Tiago Kütter; Valadares, Ana Carolina B. (Zootaxa, 2016)
This paper provides the first record of order Embioptera for the State of Tocantins, Brazil, with the description of Clothoda tocantinensis sp. nov. This genus has just three previously described species; only C. nobilis (Gerstäcker) has been recorded from Brazil (Amazon basin). An identification key is provided for males of Clothoda.